Predictors of blood volatile organic compound levels in Gulf coast residents. (June 2018) - Werder, Emily; Gam, Kaitlyn; Engel, Lawrence; Kwok, Richard; Ekenga, Christine; Curry, Matthew; Chambers, David; Blair, Aaron; Miller, Aubrey; Birnbaum, Linda; Sandler, Dale
Abstract To address concerns among Gulf Coast residents about ongoing exposures to volatile organic compounds, including benzene, toluene, ethylbenzene, o -xylene, andm -xylene/p -xylene (BTEX), we characterized current blood levels and identified predictors of BTEX among Gulf state residents. We collected questionnaire data on recent exposures and measured blood BTEX levels in a convenience sample of 718 Gulf residents. Because BTEX is rapidly cleared from the body, blood levels represent recent exposures in the past 24 h. We compared participants' levels of blood BTEX to a nationally representative sample. Among nonsmokers we assessed predictors of blood BTEX levels using linear regression, and predicted the risk of elevated BTEX levels using modified Poisson regression. Blood BTEX levels in Gulf residents were similar to national levels. Among nonsmokers, sex and reporting recent smoky/chemical odors predicted blood BTEX. The change in log benzene was −0.26 (95% CI: −0.47, −0.04) and 0.72 (0.02, 1.42) for women and those who reported odors, respectively. Season, time spent away from home, and self-reported residential proximity to Superfund sites (within a half mile) were statistically associated with benzene only, however mean concentration was nearly an order of magnitude below that of cigarette smokers. Among these Gulf residents, smoking was the primary contributor to blood BTEX levels, but other factors were also relevant.